THE RELATIONSHIP BETWEEN LEARNING ENVIRONMENT AND MOTIVATION TO LEARN OF MEDICAL FACULTY STUDENTS, MUSLIM UNIVERSITY OF INDONESIA - Yasya, Ghina Saniyyah Putri; Mokhtar, Shulhana; Harahap, Muhammad Wirawan; Amir, Suliati; Aisyah, Windy N. (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
This study aims to understand the relationship between student perceptions of the learning environment and learning motivation in students of the Faculty of Medicine at Muslim University of Indonesia. This research design uses a qualitative approach; the type of research uses an observational analytic method with a cross sectional study form. Research data comes from primary data, in analyzing data using the correlation test. The results stated that there was a positive and significant relationship between learning environment variables and learning motivation. Pearson correlation value of 0.570 with a significance of 0.000 (p < 0.05) indicates that a better learning environment correlates with a higher level of learning motivation among students. A good learning environment will play an important role in increasing students' learning motivation. Learning motivation and learning environment are closely interconnected. A positive environment, such as lecturer support and a conducive academic atmosphere, increases students' motivation to achieve academic performance.